2008
DOI: 10.1128/jvi.00586-07
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Association of the Herpes Simplex Virus Genome with Histone Proteins during a Lytic Infection

Abstract: Previous work has determined that there are nucleosomes on the herpes simplex virus (HSV) genome during a lytic infection but that they are not arranged in an equally spaced array like in cellular DNA. However, like in cellular DNA, the promoter regions of several viral genes have been shown to be associated with nucleosomes containing modified histone proteins that are generally found associated with actively transcribed genes. Furthermore, it has been found that the association of modified histones with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
148
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(161 citation statements)
references
References 30 publications
(42 reference statements)
11
148
1
1
Order By: Relevance
“…First, the entire naked DNA genome is exposed immediately after the invasion (35)(36)(37). Second, although the viral genome packages into chromatin with the host histones, it is less dense and much more loosely packed than the nuclear self-DNA (35)(36)(37). Importantly, we find that the relative binding affinity of IFI16 to various dsDNA fragments changes cooperatively not only with increasing IFI16 concentrations ( Fig.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…First, the entire naked DNA genome is exposed immediately after the invasion (35)(36)(37). Second, although the viral genome packages into chromatin with the host histones, it is less dense and much more loosely packed than the nuclear self-DNA (35)(36)(37). Importantly, we find that the relative binding affinity of IFI16 to various dsDNA fragments changes cooperatively not only with increasing IFI16 concentrations ( Fig.…”
Section: Discussionmentioning
confidence: 55%
“…Although the total amount of viral DNA would never exceed that of self-DNA, there are two features of foreign DNA that are much more conducive to filament formation by IFI16. First, the entire naked DNA genome is exposed immediately after the invasion (35)(36)(37). Second, although the viral genome packages into chromatin with the host histones, it is less dense and much more loosely packed than the nuclear self-DNA (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Although the levels of nucleosomes on the genome appear to be reduced relative to cellular DNA at later times in infection (36,40), the absolute amount of viral DNA associated with histones increases during replication (36). Additionally, it has also been observed that histone H3.1 is incorporated in a replication dependent manner (39), indicating that some level of histone assembly occurs on replicated viral DNA.…”
mentioning
confidence: 96%
“…Upon HSV-1 infection, viral genomes enter the nucleus and become "chromatinized" as the non-nucleosomal state is transformed into a chromatin structure that resembles the host genome (3,5). The assembly and modulation of nucleosomes during infection is dependent on a plethora of viral and host chromatin components (6).…”
Section: Herpes Simplex Virus (Hsv-1)mentioning
confidence: 99%